Echo Effects of Early-Life Health Shocks: The Intergenerational Consequences of Prenatal Malnutrition during the Great Leap Forward Famine in China - Jinhu Li; Nidhiya Menon (Institute of Labor Economics (IZA), 2020)
Few studies have examined the "echo effect" of early-life shocks related to prenatal malnutrition, that is, whether the legacy of such shocks is transmitted to the next generation. This study addresses this gap by leveraging extreme malnutrition during the Great Leap Forward famine in China, and by examining the intergenerational consequences of the famine on those who were not directly impacted. Using a difference-in-differences framework, we estimate the causal effect of the famine on a wide range of outcomes of children of mothers who were exposed in-utero including income, education, employment, and intergenerational income mobility; indicators that have not been considered in detail in the literature. We further contribute by using a refined measure of famine exposure at the prefecture level in rural areas, and by exploiting rich data on those directly affected and their children. We find that on average, the famine had negative echo effects on second-generation outcomes. These echo effects are primarily due to the adverse impacts on daughters, perhaps reflecting a combination of positive selection of sons born to mothers exposed to prenatal malnutrition during the famine and cultural aspects such as son preference. Our results withstand a battery of robustness and specification checks.
Keywords: I15; J62; I32; P36; N45; 330; foetal origins; great leap forward famine; malnutrition; intergenerational impacts; labour market; China